Fabrication of self-organised highly ordered titanium oxide nanotube arrays by anodic oxidation and characterisation. (6th July 2010) - Mohammadpour, Raheleh; Ahadian, Mohammad Mahdi; zad, Azam Iraji; Taghavinia, Nima, Abol Ghasem Dolati
Self-organised and vertically oriented titanium oxide nanotube array (TNTA) has been synthesised by potentiostat anodisation of Ti foil in fluoride-based electrolyte. By varying the anodisation voltage from 8 V to 24 V it was possible to gradually change the topologies of nanotubes. The size of TNTAs was measured using SEM images and also determined based on a non-destructive optical method. In addition, photoelectrochemical properties of nanotubular TiO2/Ti electrodes were examined by anodic photocurrent response, potentiodynamic polarisation measurements and electrochemical impedance spectroscopy. A general equivalent circuit model was proposed for photoelectrochemical system consists of anodic nanotubular TiO2 thin film electrode and test solution.